Assessing Current Situation of Domestic Violence against Women: A Study in Hasandaha, Morang - Pandey, Krishna P; Shrestha, Gyanendra (Himalayan Journal of Sociology and Anthropology, 2014)
Nepal like many other countries represents a multicultural characteristics having patriarchal social structure. Recognizing the need to effectively reduce the incidences of violence against women, Nepal ratified the CEDAW in 1991. But the incidences of DVAW have been repeatedly reported and the challenge to the human rights of the Nepalese women has been added. The heterogeneity of Nepalese society and social interaction among the different caste/ethnic groups make the issue of DVAW more complicated that eventually requires sociological study. The people of Hasandaha, Morang, represent the caste/ethnic heterogeneity and could be the representation of Nepalese villages. The women of that village are also suffering from multiple forms of violence against them. Physical assault, sexual abuse to psychological torture is among the forms of violence that they aspire to escape from. Rigid caste norms and patriarchal values constrict the freedom of movement among the women of Hasandaha village. These women express that the government, NGOs and civil society should have decisive roles with regard to the elimination of domestic violence against women. For this, effective mobilization of local communities, awareness generation among them and changes in the state’s attitude towards DVAW only as of private concern are key to reduce the incidences of DVAW in Hasandaha village of Morang district, Nepal. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10689 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 64-85